2022
DOI: 10.3389/fimmu.2022.868669
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Lipid Accumulation Drives the Differentiation of Decidual Polymorphonuclear Myeloid-Derived Suppressor Cells via Arachidonic Acid Metabolism

Abstract: Decidual polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) are essential to immune tolerance during pregnancy. A reduction in the number of these cells is associated with unexplained recurrent pregnancy loss (URPL). In our previous study, we reported that PMN-MDSCs are a group of mature neutrophils that are activated by the decidua microenvironment. In the present study, we show that the decidua microenvironment induces substantial lipid accumulation in neutrophils during their differentiation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…The LOX metabolic pathway in AA metabolism activates the dysregulation of hepatic glucolipid metabolism, leading to the appearance of IR and NAFLD phenotypes. Additionally, abnormal LOX metabolism maybe connected to the growth of many metabolic diseases, including fatty liver, IR, and hyperlipidemia [ 45 ]. In our study, ALOX12 protein expression was positively correlated with TC, HDLC, LDLC, and Apo B. Additionally, these results offer a fresh perspective on how lipid metabolism affects the development of tubular injury in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…The LOX metabolic pathway in AA metabolism activates the dysregulation of hepatic glucolipid metabolism, leading to the appearance of IR and NAFLD phenotypes. Additionally, abnormal LOX metabolism maybe connected to the growth of many metabolic diseases, including fatty liver, IR, and hyperlipidemia [ 45 ]. In our study, ALOX12 protein expression was positively correlated with TC, HDLC, LDLC, and Apo B. Additionally, these results offer a fresh perspective on how lipid metabolism affects the development of tubular injury in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia may also lead to the accumulation and immunosuppressive capacity enhancement of MDSCs, indicating that exogenous lipids may be taken up by MDSCs ( 11 ). In patients experiencing unexplained recurrent pregnancy loss, G-MDSC differentiation was associated with the pSTAT3/FABP5/PGE2 pathway ( 109 ). These findings are instrumental in understanding the physiological mechanisms of immune tolerance in pregnancy.…”
Section: Mdscs In Embryo Implantationmentioning
confidence: 99%
“…Spontaneous miscarriage is the loss of a pregnancy before viability with no manual intervention. This condition occurs in up to 20% of recognized pregnancies ( 109 ). As listed above, there is a reciprocal causation between MDSC deficiency and spontaneous miscarriage in the first or the second trimester.…”
Section: Mdscs During Pregnancymentioning
confidence: 99%
“…Evidence suggests that this process is mediated by inflammation, hypoxia, and environmental acidity, which in turn upregulate HIF-1α ( Corzo et al, 2010 ), PPARγ ( Xin et al, 2021 ), AMPK ( Yan et al, 2019 ), and STAT3 ( Ma et al, 2018b ). Increased eicosanoid metabolism ( Gabrilovich, 2017 ), characterized by increased COX-2 activity and concentrations of AA and prostaglandin E2 ( Prima et al, 2017 ; Wang et al, 2022 ), reciprocally increases lipid accumulation and confers immunosuppressive activity. The nitrogen metabolism is more complex, as increase in both arginase-1 ( Raber et al, 2012 ), a potent T-cell suppressor, and iNOS ( Enioutina et al, 2011 ), the pro-inflammatory NO synthase, has been reported.…”
Section: Metabolic Reprogramming Of Myeloid Cells In Cancermentioning
confidence: 99%
“…Ablating PERK, a kinase on the ER, upregulates type I interferon response and reprograms the MDSCs toward tumor-limiting myeloid cells ( Mohamed et al, 2020 ). Taken together, metabolic reprogramming of MDSCs lead to an increased expression of myeloid checkpoints [e.g., PD-L1 ( Prima et al, 2017 ; Xin et al, 2021 ) and arginase-1 ( Grzywa et al, 2020 )] and immunosuppressive cytokines [e.g., TGF-β ( Gabrilovich, 2017 ), IL-10 ( Grzywa et al, 2020 ), and PGE 2 ( Wang et al, 2022 )]. Targeting MDSC metabolism, such as lipid transport ( Al-Khami et al, 2016 )/FAO inhibitors ( Hossain et al, 2015 ; Xin et al, 2021 ), LXR agonists ( Tavazoie et al, 2018 ), and COX-2 inhibitors ( Prima et al, 2017 ), may synergize with immune checkpoint blockade and confer clinical benefit.…”
Section: Metabolic Reprogramming Of Myeloid Cells In Cancermentioning
confidence: 99%